2019
DOI: 10.1108/ijhcqa-05-2018-0107
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting quality management at the Thai national institute of health

Abstract: Purpose -The purpose of this paper is to confirm and examine organization-related factors that could affect quality management at the Thai national reference laboratory known as National Institute of Health. Design/methodology/approach -The authors invited 340 laboratory staff members to complete a questionnaire that enquired about their skills, opinions, perceptions, leadership, work environment, organizational culture and organizational commitment in relation to quality management. Confirmatory factor analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
2
5
0
Order By: Relevance
“…This negatively affects the commitment and value given to data by the healthcare providers. This finding is also consistent with studies from the Southern Nations, Nationalities, and People's Region (SNNPR) of Ethiopia ( 20 , 31 ), Iran ( 28 ), Thailand ( 33 ), Canada ( 1 ), and Kenya ( 30 ). Health facility managers and other responsible bodies usually do not use the collected data owing to reliability and accuracy problems.…”
Section: Discussionsupporting
confidence: 90%
“…This negatively affects the commitment and value given to data by the healthcare providers. This finding is also consistent with studies from the Southern Nations, Nationalities, and People's Region (SNNPR) of Ethiopia ( 20 , 31 ), Iran ( 28 ), Thailand ( 33 ), Canada ( 1 ), and Kenya ( 30 ). Health facility managers and other responsible bodies usually do not use the collected data owing to reliability and accuracy problems.…”
Section: Discussionsupporting
confidence: 90%
“…Self-leadership mainly leads to self-direction and control for a person who sets his/her own expectations. Chansatitporn et al (2019) noted that self-leadership can be found in staff members of any level who have leadership attributes within an organization and can facilitate organizational learning (Yukl, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of the operations management papers in healthcare settings have presented context specific empirical studies. Evidence related to the above directions are visible in the studies described in the research papers such as Alaloola and Albedaiwi (2008), Mustaffa and Potter (2009), Ferreira and Teixeira (2010), Walston et al (2010), Robinson et al (2012), Akpieyi et al (2015) and Chansatitporn et al (2019). These papers highlight the issues in healthcare management and institutions located in different regions.…”
Section: Introductionmentioning
confidence: 95%